Tourist perceptions of tourism destinations choice and loyalty: A perspective on developing sustainable rural tourism in Bangladesh - Bagchi, Sraboni; Ray, Shimul; Kumar, Dhanonjoy (Journal of Tourism Management Research, 2023)
Tourist perception refers to the emotional and psychological evaluations that tourists form as a result of their encounters with the destination, including its attractions, people, culture, and services. It can significantly influence tourism destination choice and loyalty, which means returning to the same destination or recommending it to others. The primary objective of this research endeavor is to investigate the perspectives held by tourists regarding their selection of destinations and their loyalty towards these destinations. The study specifically concentrates on the advancement of sustainable rural tourism within the context of Bangladesh. The study was based on quantitative methods, the study’s premise, and many statistical measurements, such as descriptive statistics, validity, reliability, regression analysis, and the study’s hypothesis. The results of the study indicate that the main determinants of tourist site selection and revisiting the tourist spots are based on the dynamic service qualities and availability of basic facilities at the tourist spots, as well as the higher propensity to reenter rural tourist places and localities. The implications for stakeholders encompass the necessity of allocating resources to develop quality services, enhance the basic facilities in tourist spots, and develop comprehensive marketing strategies aimed at promoting rural areas as attractive tourist destinations. This research makes a valuable contribution to the creation of effective strategies for sustainable development in the rural tourism industry of Bangladesh by examining tourist attitudes.